News diffusion of a significant event: how Malaysians and Indonesians learnt of the Indonesia Airasia QZ8501 tragedy - Syed Abdullah Idid, Syed Arabi; Abdul Rashid, Muhammad Shawal; Meiliyana, Ade; Mohd. Jais, Norhani (Faculty of Modern Languages and Communication Universiti Putra Malaysia, 2018)
This paper examines how a significant event is diffused in two different countries. Using the News Diffusion as a theoretical perspective, the study initially focused on the role of media in influencing the spreading of information during an enfolding aviation disaster. Taking the 2014 Indonesia AirAsia QZ8501 crash as a significant event, the research addressed the questions: How do two different nationalities learn of a significant event? How does media usage during a crisis influence the speed of news dissemination about the event? How was the spread of information on a significant event in two different nationalities was treated in different media systems? A total of 1,199 Malaysian respondents were interviewed from 5 to 14 January 2015 and another 604 respondents from 15 January to 10 February 2015 in Indonesia through the use of questionnaires. The total number of respondents in Indonesia was confided to Jambi and Jakarta because of the pressure of time needed to complete the questionnaire. The interviews took place in Jambi and Jakarta, Indonesia and nationwide for Malaysia. Data were analyzed using Statistical Package for Social Sciences (SPSS) WIN 20. Most of the respondents in Malaysia heard the news at around 01:00-01:59 p.m. (Malaysia Time) while Indonesia respondents mostly heard for the first time about the crash at 9:00- 09:59 p.m. Western Indonesia standard time (WIB) with television being the first source of news followed by Facebook as the second most common sources in spreading the news. The regularity hypothesis on the diffusion of news argues that news of a significant event is expanded more through interpersonal communication compared to mass media. This study found that the spread of news was slow, despite the event being significant. Several key themes surfaced to shed some light on the role of media in disseminating the news, the pattern of news transmission and the social-behavioural conduct in the two countries.